16S–23S rRNA intergenic spacer based molecular detection of Staphylococcus aureusdirectly from mastitic milk of crossbred cows - SHARMA, ANSHU; SINDHU, NEELESH; JAIN, v K (The Indian Journal of Animal Sciences, 2011)
The aim of the present study was to optimize 16S to 23SrRNA intergenic spacer based polymerase chain reaction assay (PCR) to detect Staphylococcus aureus directly from mastitic milk of crossbred cows. Amplified product size of 401 bp as well as that of 401bp and 511 bp in some samples was obtained using optimum concentration of magnesium ions, primers, Taq DNA polymerase and annealing temperature. Out of 730 milk samples, 101 milk samples (13.83%) were characterized as Staphylococcus aureus by bacteriological examination and other biochemical tests while PCR assay was able to detect 114 (15.61%) samples. None of the culturally positive milk sample was found negative by PCR based on 16S–23S rRNA interspacer region. The assay could detect organisms even when they are not viable due to antibiotic therapy. Molecular detection of Staphylococcus aureus by PCR assay was rapid, sensitive and specific, and can be used for screening large dairy herd for early and faster detection; thereby establishment of effective preventive measures reducing economic losses.